2011
DOI: 10.1681/asn.2011020203
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Uptake by S1 Proximal Tubular Segment Causes Oxidative Stress in the Downstream S2 Segment

Abstract: Gram-negative sepsis carries high morbidity and mortality, especially when complicated by acute kidney injury (AKI). The mechanisms of AKI in sepsis remain poorly understood. Here we used intravital two-photon fluorescence microscopy to investigate the possibility of direct interactions between filtered endotoxin and tubular cells as a possible mechanism of AKI in sepsis. Using wild-type (WT), TLR4-knockout, and bone marrow chimeric mice, we found that endotoxin is readily filtered and internalized by S1 proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
162
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 146 publications
(168 citation statements)
references
References 54 publications
5
162
1
Order By: Relevance
“…Results presented extend previous studies of cultured cells, demonstrating that rifampin inhibits uptake of organic anions by hepatocytes in vivo and provide support for an iterative model of hepatic transport. Although used here to evaluate the effects of chronic rifampin treatment, the ability to analyze processes occurring in the timescale of seconds to minutes also provides intravital microscopy with the unique ability to detect acute, or transient drug effects which, when combined with additional readouts of injury, 43,60,[62][63][64][65][66] provides the potential to characterize the chronology of cholestatic liver injury. Since is both properly sedated and physiologically supported.…”
Section: Discussionmentioning
confidence: 99%
“…Results presented extend previous studies of cultured cells, demonstrating that rifampin inhibits uptake of organic anions by hepatocytes in vivo and provide support for an iterative model of hepatic transport. Although used here to evaluate the effects of chronic rifampin treatment, the ability to analyze processes occurring in the timescale of seconds to minutes also provides intravital microscopy with the unique ability to detect acute, or transient drug effects which, when combined with additional readouts of injury, 43,60,[62][63][64][65][66] provides the potential to characterize the chronology of cholestatic liver injury. Since is both properly sedated and physiologically supported.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 1 million bone marrow cells obtained from the long bones of donor mice were transplanted via the lateral tail vein as described previously. 31 Eight weeks after bone marrow transfer, the degree of chimerism was assessed by flow cytometry using CD45.1 (BoyJ) and CD45.2 (p53 2/2 ) antibodies (Becton Dickinson; Supplemental Figure 2). …”
Section: Creation Of Chimeric Micementioning
confidence: 99%
“…Several groups have recently utilized intravital microscopy to try to answer these questions. First, Dagher et al have shown that fluorescently labelled endotoxin [lipopolysaccharide (LPS)] is filtered by the kidney and taken up in early (S1) proximal tubule segments [37]. However, rather than directly causing damage in this segment, evidence of oxidative stress was surprisingly observed downstream in later S2 segments, perhaps due to some kind of crosstalk process, involving paracellular communication.…”
Section: Sepsis and Acute Kidney Injurymentioning
confidence: 99%